2018
DOI: 10.1122/1.5042521
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear rheology of poly(ethylene-co-methacrylic acid) ionomers

Abstract: Using a parallel-plate rheometer equipped with a partitioned plate, and the Sentmanat extensional rheometer fixture, a full rheological characterization of several commercial ionomers and their corresponding parent copolymers has been carried out. Particular emphasis has been placed on the distribution of the relaxation times to identify the characteristic times, such as reptation, Rouse, and sticky-Rouse, that are associated with the characteristic lifetime of the ionic and hydrogen bonding associations. As s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The lifetime of these ionic bridges depends on their ionic environment and appears to shorten with increasing monovalent cation (mainly potassium) concentration. Usually, the sticker lifetime is described using an empirical Arrhenius form , where the activation energy is determined from the linear rheology using Van ’t Hoff plots [ 13 , 23 , 26 , 40 , 51 , 52 , 53 ]. In this section, we argue that this activation energy might not be the one that is of importance to the non-linear rheology, because a different mechanism of sticker opening takes over.…”
Section: Experimental and Modelling Methodsmentioning
confidence: 99%
“…The lifetime of these ionic bridges depends on their ionic environment and appears to shorten with increasing monovalent cation (mainly potassium) concentration. Usually, the sticker lifetime is described using an empirical Arrhenius form , where the activation energy is determined from the linear rheology using Van ’t Hoff plots [ 13 , 23 , 26 , 40 , 51 , 52 , 53 ]. In this section, we argue that this activation energy might not be the one that is of importance to the non-linear rheology, because a different mechanism of sticker opening takes over.…”
Section: Experimental and Modelling Methodsmentioning
confidence: 99%
“…The low-energy mechanism for natural silk-spinning therefore remains to be identified. Clues may be present in the subtle electrostatically-modified rheo-physics of associating polymers [12][13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…We previously found in collaboration with Laity and Holland that the silk protein exhibits intermolecular reversible cross-links [7,22]. While these associations shift the alignment-tostretch transition to smaller strain rates by replacing the usual Rouse relaxation dynamics for 'sticky Rouse' relaxation [12][13][14][15][16][17][18][19][20][21], this is not the full story, for the Bombyx mori silkworm manages also to generate the opposite effect during pupation: when the silkworm starts spinning the material it actually chemically reduces this relaxation time through the addition of potassium cations [7,22]. Intriguingly, the group of Holland discovered that the structural features of the silk fibre is significantly enhanced through a gradient in the pH along the spinning duct, suggesting an exquisitely controlled local rheology [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that microscopic chain stretch and the consequent macroscopic strain hardening is triggered by a small number of calcium bridges [13,15] that act as 'sticky' reversible intermolecular crosslinks akin to those in synthetic 'sticky polymers' [16][17][18][19][20][21][22][23][24]. For this class of molecules, a molecular understanding of the non-linear rheology and crystallization of 'sticky polymers' has so far relied on computationally expensive (coarse-grained) molecular dynamics simulations [5,[25][26][27][28][29]. Simpler molecular models coarse-grained at the level of entanglements, but able to capture the vital slow processes, remain absent.…”
mentioning
confidence: 99%
“…open [13,17,[24][25][26][27][28], and the closing rate is given by k close = k open p/(1 − p), with p the time-or ensemble-averaged fraction of closed stickers. Here, we ignore the underlying dissociation-association or bondswap mechanisms that determine the concentrationdependence of the opening and closing rates [40,41], and view p and τ s as free model parameters.…”
mentioning
confidence: 99%